2018
DOI: 10.1091/mbc.e18-01-0057
|View full text |Cite
|
Sign up to set email alerts
|

Genetically induced microtubule disruption in the mouse intestine impairs intracellular organization and transport

Abstract: In most differentiated cells, microtubules reorganize into noncentrosomal arrays that are cell-type specific. In the columnar absorptive enterocytes of the intestine, microtubules form polarized apical–basal arrays that have been proposed to play multiple roles. However, in vivo testing of these hypotheses has been hampered by a lack of genetic tools to specifically perturb microtubules. Here we analyze mice in which microtubules are disrupted by conditional inducible expression of the microtubule-severing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Therefore, it will be important to determine what mediates the transcriptional response and whether it is directly responsible for the contractility or a feedback mechanism that amplifies it. Notably, we find that this cellular response to microtubule disruption is not universal, as microtubule disruption in differentiated cells of the intestinal epithelium did not result in a similar contractility phenotype 59 . Consistent with this, the upregulation of contractility-related genes was not noted upon microtubule disruption in cultured retinal pigment epithelium cells, suggesting distinct responses of different cell types to microtubule disruption 60 .…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, it will be important to determine what mediates the transcriptional response and whether it is directly responsible for the contractility or a feedback mechanism that amplifies it. Notably, we find that this cellular response to microtubule disruption is not universal, as microtubule disruption in differentiated cells of the intestinal epithelium did not result in a similar contractility phenotype 59 . Consistent with this, the upregulation of contractility-related genes was not noted upon microtubule disruption in cultured retinal pigment epithelium cells, suggesting distinct responses of different cell types to microtubule disruption 60 .…”
Section: Discussionmentioning
confidence: 71%
“…In this context, the misplacement of a number of organelles was also observed Wang et al, 2016). Additionally, conditional expression of Spastin, which encodes a MT-severing protein, in the mouse intestine resulted in misplacement of organelles (Muroyama et al, 2018). These studies indicate that MT filaments organization are essential for the establishment of intestinal cell shape and organelle distribution.…”
Section: Loss-of-function Intestinal Phenotypementioning
confidence: 84%
“…As previously described in the Introduction, γ-TuRC is essential for both MT nucleation at the centrosome and MT stabilization as it acts as a minus-end-capping protein complex (Anders and Sawin, 2011;Wiese and Zheng, 2000;Zheng et al, 1995). In differentiated intestinal cells, however, the major γ-TuRC-component γtubulin is redeployed to the apical nc-MTOC (Ameen et al, 2001;Muroyama et al, 2016Muroyama et al, , 2018Salas, 1999). Ameen et al (2001) showed that in the intestine of Ck8deficient mice, differentiated cells lacked CIFs and the localization of γ-tubulin was found to be dispersed within the cytoplasm of enterocytes, in contrast to its normal apical membrane localization.…”
Section: Is a Novel Centrosomal Proteinmentioning
confidence: 98%
See 2 more Smart Citations